ANALISIS KINERJA KEUANGAN BERDASARKAN METODE ECONOMIC VALUE ADDED PADA KOPERASI PRIMER KEPOLISIAN RESORT KOTA MOJOKERTO - Iskharimah . (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This research aims to determine the financial performance based on Economic Value Added in showing real SHU changes in the Mojokerto City Police Primary Cooperative, and to know the financial performance based on Economic Value Added in creating added value in the Mojokerto City Primary Police Cooperative. The research method used descriptive research through quantitative research. Data was collected by literature review and field research through interviews, observations and documentation. Research problem analyzed using Economic Value Added (EVA) analysis. The results showed that there was a realization of revenue that was not in accordance with the plan. Therefore the impact on the achievement of the SHU Cooperative was not optimal. In addition, the calculation of financial statements using the Economic Value Added (EVA) analysis of financial statements of Mojokerto City Police Primary Cooperatives in shows that in the period 2011-2013 the Mojokerto City Primary Police Cooperatives have not be able to create economic added value for members of the cooperatives, creditors as well as other interested parties.